Analisis Budidaya Kepiting dalam Meningkatkan Kesejahteraan Ekonomi pada Petani Kepiting di Desa Labotto Kecamatan Cenrana - Sulastri, Irma; Hafid, Abd; Munawarah, Munawarah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to contribute to understanding crab cultivation in improving the economic welfare of crab farmers in Labotto Village, Cenrana District. In Labotto Village, crab cultivation has become a source of income for the people in Labotto Village who work as crab farmers, which is supported by supportive natural conditions and high market demand for crabs. The type of approach used in this research is field research with a qualitative descriptive approach, namely a research approach that seeks to explain an event or happenings that are currently occurring. Then the data collection techniques used in this research were observation, interviews and documentation. Based on the results in this research, it shows that crab cultivation can have a positive impact on increasing the income of crab farmers and the community in Labotto Village who also participate in the Crab Cultivation Process. Success in crab cultivation is influenced by several factors, including the availability of natural resources, the skills of crab farmers, business capital, and access to markets. Crab Farmers who have good knowledge and skills in cultivating crabs, and are able to access markets more effectively, in the results of this research show a higher increase in income while cultivating crabs. The conclusion from the results of this research is that crab cultivation has great potential to improve the economic welfare of the community in Labotto Village because crab cultivation also opens up employment opportunities during the cultivation stage, starting from the Management, Maintenance, to the crab harvesting process. However, to ensure sustainability and improvement in crab cultivation, additional efforts are needed such as increasing access to modern technology, developing marketing networks, and policies that support the growth of crab cultivation. Thus, crab cultivation can be a strategic solution in improving the economic welfare of the community in Labotto Village.